The evolving landscape of new diagnostic tests for invasive aspergillosis in hematology patients: strengths and weaknesses - Buchheidt, Dieter; Hofmann, Wolf-Karsten; Spiess, Birgit; Boch, Tobias (Current opinion in infectious diseases, 2017)
The diagnosis of invasive aspergillosis in hematologic patients is a complex composite of clinical preconditions and features, imaging findings, biomarker combinations from appropriate clinical samples and microbiological and/or histological findings. Recent developments in the evolving landscape of diagnostic tests for invasive aspergillosis in adult hematology patients are highlighted. Novel approaches and tools are currently under development. Focusing optimized diagnostic performance, in particular the combination of biomarkers from appropriate clinical samples, improved diagnostic performance distinctly.